Rome - Leach, Andrew 1976- (Cambridge, United Kingdom Polity Press, 2017)
"Rome has a history unmatched in richness by any city on the globe. It looms large in the word's cultural imagination, and for millennia it has been a meeting point of great cultures, a place where myth mixes freely with history, leaving neither unscathed. In this compact history, Leach demonstrates what most visitors to the Eternal City will instinctively understand: that the buildings, streets, monuments and gardens of this ancient city give the visitor moments of direct communion with its past. He reveals the long, twisting history of Rome through its ruins, art works and monuments, its metro stations and modern apartment blocks. Each chapter takes the reader on a physical journey invoking Rome in different moments of its life. Engaging historical narrative is supplemented with maps and photos, making Rome an indispensable companion for those who want to dig below the city's surface"--Publisher
Introduction: thinking about seeing -- 1. A matter of foundations -- 2. Roma caput mundi -- 3. A middle age -- 4. Return to Rome -- 5. The capital of Italy.
Includes bibliographical references (pages 286-290) and indexes.
Keywords: Rome (Italy) -- History; Rome (Italy) -- Description and travel